Task Difficulty Regulates How Conscious and Unconscious Monetary Rewards Boost the Performance of Working Memory: An Event-Related Potential Study - Xu, Shiyang; Qi, Senqing; Duan, Haijun; Zhang, Juan; Akioma, Miriam; Gao, Fei; Wu, Anise M. S.; Yuan, Zhen (Frontiers in Systems Neuroscience, 2022)
The performance of working memory can be improved by corresponding high vs. low-value rewards consciously or unconsciously. However, whether conscious and unconscious monetary rewards boosting the working memory performance is regulated by the difficulty level of working memory task is unknown. In this study, a novel paradigm that consists of a reward-priming procedure and N-back task with various levels of difficulty was designed to inspect this cognitive processing. In particular, both a high-value and low-value coin were presented consciously or unconsciously as the reward procedure, followed by the N-back task, during which EEG recordings were also carried out. It was discovered that the high-value reward elicited larger event-related potential component P3 along the parietal area (reflecting the working memory load) as compared to the low-value reward for the low-difficulty 1-back task whether the reward was unconsciously or consciously presented. By contrast, this is not the case for the high-difficulty 2-back task, in which the difference in P3 amplitude between the high-value and low-value reward was not significant for the unconscious reward case although exhibited significance for the conscious reward processing. Interestingly, behavior analysis results also exhibited very similar patterns as ERP findings. Therefore, the present work demonstrated that the task difficulty level can modulate the influence of subliminal reward on working memory performance.